Performance Comparison of Field-oriented Control, Direct Torque Control, and Model-predictive Control for SynRMs - Hadla, Hazem (2022)
Simulation studies of three synchronous reluctance motor (SynRM) control strategies are presented: field-oriented control (FOC), direct torque control (DTC), and finite-set model-predictive control (FS-MPC). FOC uses linear controllers and pulse-width modulation to control the fundamental components of the load voltages vectors. In contrast, DTC and FS-MPC are nonlinear strategies wherein the voltage vectors are directly generated in the absence of a modulator. Theoretical operating principles and control structures of these control strategies are presented. Moreover, a comparative analysis of the static and dynamic performance of the control strategies is conducted using Matlab/Simulink to identify their advantages and limitations. It is confirmed that each of the control strategies has merits and that all three of them satisfy the requirements of modern high-performance drives.